A plague of sheep environmental consequences of the conquest of Mexico - Melville, Elinor G. K. (Studies in environment and history., 1994)
This is a book about the biological conquest of the New World. Taking as a case study the sixteenth-century history of a region of highland central Mexico, it shows how the environmental and social changes brought about by the introduction of Old World species aided European expansion. The book spells out in detail the environmental changes associated with the introduction of Old World grazing animals into New World ecosystems, demonstrates how these changes enabled the Spanish takeover of land, and explains how environmental changes shaped the colonial societies.